Draft Five Year Plan 1978-83 Union Territory of Lakshadweep - Planning Commission (Planning Commission, 1978)
There was no integrated First Five Year Plan for these islands. Attempts were made in the middle of II Five Year Plan to implement an integrated shirt term plan in the islands with an outlay of Rs.73.05 lakhs. Actual expenditure during the second plan was Rs.40.28 lakhs.
Planning Cell Secretariat, Lakshadweep, Kavaratti